3-Dimensional assessment of tricuspid annular geometry after percutaneous edge-to-edge repair in patients with severe tricuspid regurgitation. (25th November 2020) - Da Rocha E Silva, J.G; Ruf, T.F; Kreidel, F; Tamm, A.R; Geyer, M; Petrescu, A; Hell, M; Schmidt, P; Tang, G.H.L; Munzel, T; Von Bardeleben, R.S
Abstract: Background: Transcatheter tricuspid valve repair (TTVR) using edge-to-edge leaflet therapy (E2E) has evolved as a feasible therapy to treating severe tricuspid regurgitation (TR). The TRILUMINATE trial using the new TriClip NT has shown promising clinical and functional improvements. However, the 3rd generation MitraClip XTr (Abbott Structural Heart, Santa Clara, CA, USA) has a broad off-label experience in the European Union to address tricuspid TR with wider gaps. There is insufficient data on the secondary effects of E2E on tricuspid annular geometry. The aim of this study was to address this lack of knowledge by evaluating the acute effects of E2E using the MitraClip XTr. Methods: We retrospectively analyzed the imaging data of procedures using the MitraClip XTr to treat severe symptomatic TR at our Institution in 2018. Tricuspid annular geometry was assessed before and immediately after clip implantation by 3D TEE analysis of biplane and manual and automated volume data. Results: During 2018, 69 patients were treated for severe TR using a transcatheter approach. In 61 patients, E2E was used, in 58 patients the MitraClip XTr was utilized (Pascal: n=3, Edwards Lifesciences, Irvine, CA, USA). Mean age was 79.0 years ± 6.4. Percutaneous TTVR using the MitraClip XTr significantly decreased the diastolic septal-lateral diameter (S/L: 4.1±0.7cm vs. 3.6±0.7cm; p<0.001), annulus area (14.9±6.7 vs. 12.8±6.2 cm 2 ; p<0.001) and annulus perimeter (14.7±25.0 vs. 13.8±24.4 cm; p<0.001) whereas the diastolic anterior-posterior diameter was not significantly affected (A/P: 4.5±1cm vs. 4.4±0.8cm; p=0, 45). Conclusions: Percutaneous TTVR using MitraClip XTr showed significant changes in TV annulus geometry by focal perimeter and area reduction. This highlights a new mechanism of E2E therapy through indirectly adressing the dilated annulus in patients with severe TR. Funding Acknowledgement: Type of funding source: None